Essential of Writing / Vincent F. Hopper, Cedric Gale, and Benjamin W. Griffith - Hopper, Vincent F. (New York (State) : Barron`s, 2000)
Trata de Essential of Writing.
1. Identifying Nouns 2. Possessive case of nouns
incluye índice
Col. Educ
Keywords: 1. IDENTIFYYING PREDICATE 2. DETECTING COMMA FAULTS